Investigation of the Distribution of Thalassemia in Children in Jiangxi Province, the People's Republic of China. (3rd September 2022) - Wang, Ke; Yi, Ting; Wu, Wen-Tao; Lu, Juan; He, Li-Na; Zhou, Hong-Ping; Ke, Jiang-Wei; Liu, Fa-Di
Abstract: Thalassemia is one of southern China's most common inherited disorders. Little is known about the genotypes of thalassemia in children in Jiangxi Province, the People's Republic of China (PRC). Two thousand, nine hundred and fifty-two children with suspected thalassemia were recruited from August 2016 to December 2020 at the Jiangxi Provincial Children's Hospital, Nanchang, PRC. Reverse dot-blot hybridization was used to detect α- and β-thalassemia (α- and β-thal) genotypes. A rare mutation was detected using gap-polymerase chain reaction (gap-PCR) and gene sequencing. The overall distribution of thalassemia (1534 cases) was 51.96%, and the detection rate of α-thal (616 cases), β-thal (888 cases) and concurrent α- and β-thalassemias (30 cases) was 20.86, 30.08, and 1.02%, respectively. A rare α-thal genotype, –α 27.6 /– – SEA (Southeast Asian), was identified. Seventy-eight cases of severe β-thal were detected, accounting for 8.78% of the cases, including 56 double heterozygous cases and 22 cases that were homozygous. Both α- and β-thalassemias are widely distributed in the children of Jiangxi Province. Thalassemia genetic testing is essential to establish a comprehensive thalassemia prevention program and improve public education.